ANALISIS STUDI KELAYAKAN BISNIS UMKM TOKO HILMIAS DI KECAMATAN BENGKALIS : TINJAUAN DARI ASPEK MANAJEMEN ,ASPEK HUKUM, PASAR DAN PEMASARAN, DAN ASPEK SUMBER DAYA MANUSIA - M. Farid Ilham; Mimi Nazrah; Gustrina Sari; Puji Afriyeni (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze the business feasibility of Toko Hilmi AS which is engaged in creative products in the form of buckets from five main aspects, namely law, market and marketing, management, and human resources (HR). This research uses a descriptive qualitative method with a case study approach conducted through interviews, direct observation, and document studies. The results showed that Toko Hilmi AS has fulfilled the business legality aspect through the ownership of a Business Identification Number (NIB), and has carried out a marketing strategy that adapts to market trends and needs. The simple yet efficient management structure and reward system for employees are also an added value in the HR aspect. These findings indicate that Toko Hilmi AS is a viable business to be further developed by strengthening the recording system and digital promotion.